Answer:
x = 1
y = 5
Step-by-step explanation:
5x - 2y = -5
5x + 6y = 35
=> 5x + 6y = 35
=> 5x - 5x + 6y = 35 - 5x
=> 6y = 35 - 5x
=> 6y/6 = 35/6 - 5/6x
=> y = 35/6 - 5/6x
=> 5x - 2 (35/6 - 5/6x) = -5
=> 5x - 35/3 + 5/3x = -5
=> 15/3x -35/3 + 5/3 = -15/3
=> 20/3x -35/3 = -15/3
=> 20/3x -35/3 + 35/3 = -15/3 + 35/3
=> 20/3x = 20/3
=> 20/3x * 3 = 20/3 * 3
=> 20x = 20
=> 20x/20 = 20/20
=> x = 1
=> 5x + 6y = 35
=> 5(1) + 6y = 35
=> 5 + 6y = 35
=> 5 -5 + 6y = 35 -5
=> 6y = 30
=> 6y/6 = 30/6
=> y = 5
So, x = 1
y = 5